Reforming the National Commission on Human Rights' Authority in Enforcing Gross Human Rights Violations in Indonesia - Yesica Nur Wardana; Aries Isnandar; Yogi Prasetyo (Constitutionale, 2026)
The enforcement of gross human rights violations in Indonesia continues to face significant normative and institutional challenges, particularly in the relationship between the National Commission on Human Rights (Komnas HAM) and the Attorney General's Office under Law No. 26 of 2000 on Human Rights Courts. In practice, the resolution of such cases is often delayed by repeated returns of investigation files, weak inter-agency coordination, and the limited authority of Komnas HAM, which is restricted to preliminary investigations without investigative or prosecutorial powers. This study examines the weaknesses in the current allocation of authority and proposes institutional reforms from constitutional law and human rights perspectives. This research employs a normative legal method using statutory, conceptual, and case approaches. Lawrence M. Friedman's legal system theory provides the analytical framework for assessing the structural and substantive dimensions of human rights enforcement in Indonesia. The findings indicate that Komnas HAM's dependence on the Attorney General's Office at the investigation and prosecution stages has contributed to legal uncertainty and impeded the fulfillment of victims' rights to justice. The study further finds that Law No. 26 of 2000 does not provide a clear mechanism for following up on Komnas HAM's findings or establish time limits for case resolution. The study contributes to the literature by proposing reforms grounded in state responsibility and victims' rights. It recommends amending Law No. 26 of 2000 to strengthen institutional coordination, establish mandatory follow-up procedures for Komnas HAM's findings, and enhance the protection of victims' rights within Indonesia's human rights enforcement framework.